A dietary cholesterol challenge study to assess Chlorella supplementation in maintaining healthy lipid levels in adults: a double-blinded, randomized, placebo-controlled study. Issue 1 (December 2015) - Kim, Sangmi; Kim, Joohee; Lim, Yeni; Kim, You; Kim, Ji; Kwon, Oran
Abstract Background Previous animal studies suggested thatChlorella, a unicellular green alga, has a preventive role in maintaining serum cholesterol levels against excess dietary cholesterol intake. This study aimed to conduct a pioneering investigation to clarify this issue in healthy subjects by adopting a dietary cholesterol challenge, which has not been used previously in similar studies ofChlorella in hypercholesterolemia. Methods In this double blind, randomized, placebo-controlled study, 34 participants ingested 510 mg of dietary cholesterol from three eggs concomitantly with a usual dose ofChlorella (5 g/d) or a matched placebo for 4 weeks. Results The dietary cholesterol challenge induced consistently higher concentrations of serum total cholesterol (TC, P < 0.001), LDL-C (P = 0.004), and HDL-C (P = 0.010) compared with baseline values, suggesting that the challenge was reliable. Thus, we observed a preventive action ofChlorella in maintaining serum TC versus placebo levels (3.5 % versus 9.8 %, respectively;P = 0.037) and LDL-C versus placebo levels (1.7 % versus 14.3 %, respectively;P = 0.012) against excessive dietary cholesterol intake and in augmenting HDL-C versus placebo levels (8.3 % versus 3.8 %, respectively). Furthermore, serum α-carotene showed the best separation between the placebo andChlorella groups (R2 X and R2 Y > 0.5; Q2 > 0.4). Conclusion The results suggest that a fully replicated dietary cholesterol challenge may be useful in assessing the effectiveness of dietary supplements in maintaining the serum lipid profiles of adults whose habitual diets are high in cholesterol. Trial registration WHO International Clinical Trials Registry Platform (KCT0000258 )